2019
DOI: 10.1101/856005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primate-restricted KRAB zinc finger proteins and target retrotransposons control gene expression in human neurons

Abstract: In the first days of embryogenesis, transposable element-embedded regulatory sequences (TEeRS) are silenced by Kruppel-associated box (KRAB)-zinc finger proteins (KZFPs).Many TEeRS are subsequently coopted in transcription networks, but how KZFPs influence this process is largely unknown. We identify ZNF417 and ZNF587 as primate-specific KZFPs repressing HERVK (human endogenous retrovirus K) and SVA (SINE-VNTR-Alu) integrants in human embryonic stem cells (ESC). Expressed in specific regions of the human devel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Epigenetic modifier drugs (DNMT and HDAC inhibitors) induce transcription from LTRs and lead to a high number of chimeric RNAs [177]. It was recently shown that primate‐specific KRAB zinc finger proteins and their target retrotransposons control gene expression in human neurons [178]. Activation of LINE‐1 elements was also shown in human neuronal progenitors following global DNA demethylation [12].…”
Section: Tes As Potential Pathogenic Driversmentioning
confidence: 99%
“…Epigenetic modifier drugs (DNMT and HDAC inhibitors) induce transcription from LTRs and lead to a high number of chimeric RNAs [177]. It was recently shown that primate‐specific KRAB zinc finger proteins and their target retrotransposons control gene expression in human neurons [178]. Activation of LINE‐1 elements was also shown in human neuronal progenitors following global DNA demethylation [12].…”
Section: Tes As Potential Pathogenic Driversmentioning
confidence: 99%
“…To identify ORFs whose start codons derive from transposable elements, we intersected our ORF start codons with a TE annotation kindly provided by the lab of Dr. Didier Trono. 60 First, we created a list of all start codons in different categories (protein-coding, lncRNA, uORF, sORF, pseudogene) by collapsing all ORFs that share a start position. We extended this start codon position to a 10 bp window and intersected this with a bed file of all TEs in the human genome using BedTools.…”
Section: Transposable Element Insertion At Start Codonsmentioning
confidence: 99%
“…S1) (Miller et al 2014; Li et al 2018). To enrich for different small RNA moieties, we separated sequencing reads into lengths of 18 - 25bp, 26 – 37bp and 38 – 50bp and intersected with Ensembl annotations, miRBase, the GtRNAdb database and our modified merged TE RepeatMasker data set (Kozomara and Griffiths-Jones 2014; Chan and Lowe 2016; Pontis et al 2019; Turelli et al 2020; Yates et al 2019; Playfoot et al 2021). As expected, the different read lengths enriched for annotated miRNAs, tRNAs and snoRNAs respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%